Community Health Assessment of Waste Management in Keelek Sub–District Municipality, Mae Rim District, Chiang Mai Province - Jaitae, Samart; Rattanapunya, Siwalee; Stantripop, Janjiraporn; Moolphate, Saiyud (Journal of Multidisciplinary Academic Research and Development (JMARD), 2026)
This mixed-methods study aimed to (1) assess community health impacts associated with municipal solid waste management and (2) synthesize participatory policy recommendations to reduce and prevent health impacts at the community level. The quantitative sample consisted of 382 households residing in Kee Lek Subdistrict Municipality, Mae Rim District, Chiang Mai Province, Thailand. In addition, 12 key informants who were stakeholders in community solid waste management participated in the qualitative component. Data collection instruments included structured questionnaires, informal interviews, and focus group discussions. Quantitative data were analyzed using descriptive statistics and multiple regression analysis, while qualitative data were analyzed through content analysis. The findings revealed that the community solid waste management mechanism primarily operated at the household level, where waste was collected and subsequently transported by a private company for final disposal. The overall level of community health impact was high (𝑥̅ = 3.54 ± 0.56). Factors that significantly predicted community health impacts at the 0.05 level included household size (B = −0.040, p = 0.020) and attitudes toward community solid waste management (B = 0.694, p < 0.001). Policy recommendations to reduce and prevent community health impacts include promoting the 3Rs concept (Reduce, Reuse, Recycle) and establishing a community waste bank to enhance participation and support sustainable waste management practices at the local level.